Short-term application of diquafosol ophthalmic solution benefits children with dry eye wearing orthokeratology lens - Yang, Yuanfang; Wu, Qinghui; Tang, Yao; Wu, Haoran; Luo, Zhiwei; Gao, Wenyu; Hu, Ziqi; Hou, Lijun; Wang, Min; Yang, Zhikuan; Li, Xiaoning (Frontiers in Medicine, 2023)
Purpose: To evaluate the effect of 3% diquafosol ophthalmic solution (DQS) on children with dry eye wearing overnight orthokeratology (OrthoK).: Myopic children aged 8 to 18 years with dry eye were enrolled in this prospective observational study, they were grouped according to OrthoK treatment history for at least one year. All participants received DQS four times per day for one month. The following indicators were measured at baseline and one month after treatment: Dry Eye Questionnaire-5 (DEQ-5), Noninvasive Tear Meniscus Height (TMH), Noninvasive Tear Film Break-up Time (first and average, NIBUT-F and NIBUT-A), meibomian gland score (MG score), conjunctival hyperemia redness score (R-scan), and blink pattern analysis. Results: One hundred four participants (189 eyes) including 40 OrthoK wearers (72 eyes) and 64 OrhtoK candidates (117 eyes) completed the study. Of all, after DQS treatment for one month, DEQ-5 scores reduced from 5.54±3.25 to 3.85±2.98 (t=-3.36, p=0.00). TMH increased from 0.20±0.05 mm to 0.21±0.05 mm (t=2.59, p=0.01),NIBUT-F and NIBUT-A were prolonged from 6.67±4.71 s to 10.32±6.19 s and from 8.86±5.25 s to 13.30±6.03 s (all p=0.00), respectively. R-scan decreased from 0.69±0.28 to 0.50±0.25 (t=-9.01, p=0.00). Upper MG scores decreased from 1.04±0.32 to 0.97±0.36 (t=-2.14, p=0.03). Lower MG scores, partial blink rate, partial blinks, and total blinks did not change significantly. BUT and R-scan both improved significantly after DQS treatment for one month (all p=0.00) in OrthoK candidates and OrthoK wearers. Among the OrthoK wearers, TMH and dry eye symptoms increased significantly (all p=0.00), but not in OrthoK candidates (p>0.05). There were no adverse events related to DQS.: Diquafosol Ophthalmic Solution was effective for children wearing overnight orthokeratology in relieving dry eye symptoms and improving ocular surface parameters, which may help improve children's OrthoK wearing tolerance and compliance.